THE SPIRITUAL HERITAGE OF THEJADIDS: PHILOSOPHICAL AND SYNERGETIC ANALYSIS - Jafar Mustafayev; Vokhidjon Jurakulov (Academia Science Repository, 2023)
This article presents socio-philosophical and synergetic considerations about the influence of spiritual heritage on the development of society, as well as about our ancestors’ rich spiritual and cultural values. In addition, the multifaceted aspects of the spiritual heritage of the Jadids characteristic of their time and the merits of the Turkic peoples in implementing a new system of reforms combining the principles of religion, values, customs, traditions, nationalism and humanity were also highlighted. The article approaches spiritual heritage from the point of view of national and religious values. At different times, there have been different approaches and attitudes to towards the customs and traditions of nations and national and spiritual heritage. All the views and aspirations of our thinkers are actually aimed at encyclopaedic knowledge aimed at increasing and preserving national and spiritual heritage. Moreover, in today's era of information and globalization, a coherent and paradigmatic approach is very important. A consistent and paradigmatic approach is evident in the spiritual movement of the Jadids. Additionally, their use of synergetic methodology in the matter of spiritual heritage served the people of Turan land to develop the concepts of national pride, pride, freedom, freedom, independence, national thinking and religious belief, intellectuality, and national consciousness. The article reveals that the nation, the state or the region does not fall into spiritual dependence, and geopolitically complete sovereignty is in many cases connected with the synergistic features of spiritual heritage.